The Influence of Leadership and Workload on Employee Performance at CV. XYZ - Yohanas, Alicia Angela; Hasanuddin Hasanuddin; Jumawan Jumawan; Fauzi, Achmad; Setyawati, Novita Wahyu (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The purpose of this research is to analyze the influence of Leadership and Workload on Employee Performance at CV. XYZ. The research methodology used in this study is a quantitative approach. The sampling technique in this study used a census sample involving 42 employees as respondents. Data collection techniques were carried out using a questionnaire consisting of several statements and measured using the Likert Scale. Data analysis was conducted using the Structural Equation Modeling (SEM) method. Data were processed using SmartPLS 4.1 software. The research findings indicate that Leadership (X1) has a positive and significant impact on Employee Performance. Additionally, Workload (X2) also has a positive and significant impact on Employee Performance.